Does lack of innovation and absorptive capacity retard economic growth in Africa? - Steve Onyeiwu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
This paper reviews the innovative capabilities and absorptive capacities of African countries, and investigates whether they have played significant roles in the region's slow and episodic economic growth. Results from cross-country regressions covering 31 Sub-Saharan African countries suggest that growth in Africa is not simply a question of capital accumulation, fertility rates, aid dependency, and stable macroeconomic environment. It is also about strengthening the capacity of African countries to assimilate and effectively use knowledge and technology. Contrary to the views held by many analysts, the growth of African economies does not depend so much on their ability to innovate, but rather on their capacity to absorb and effectively use new technologies. Beyond technological issues, the paper confirms the stylized facts that the size of the government and political stability are important for the growth performance of African countries.
Keywords: O33; O43; O55; 330; growth; innovation; absorptive capacity; technology; Africa; Wirtschaftswachstum; Innovation; Absorption; Afrika; Afrika südlich der Sahara